Phonological Variation in World Englishes: A Comparative Analysis - Pereira, Maria; Siswandi, Siswandi; Aldino Hadi, Kanti (Journal of Humanities Research Sustainability, 2025)
Background. English is a global language with numerous regional and social varieties, each exhibiting unique phonological characteristics. These variations are shaped by diverse social, cultural, and geographical influences, leading to significant differences in pronunciation across different English-speaking communities. In the context of cross-cultural communication, these phonological differences can either enhance cultural identity or create barriers to mutual understanding. Purpose. This study aims to explore how phonological variations manifest across different varieties of English spoken around the world. It also seeks to investigate how social, cultural, and geographical factors contribute to these variations, and how they influence the perception and understanding of speech in cross-cultural communication. Furthermore, the research examines the role of these phonological variations in constructing and reflecting the social identity of speakers. Method. The study employs a qualitative research approach combined with phonetic analysis to examine specific phonological features. Data collection methods include in-depth interviews with speakers from various English varieties and the application of advanced acoustic analysis technology to identify key phonetic variations. This combination of qualitative and technological methods provides a comprehensive understanding of the sociophonetic landscape of global English. Results. The results reveal substantial phonological differences across different varieties of English. These include vowel shifts, distinct consonant cluster patterns, varying intonation contours, differing degrees of rhoticity, and contrasts between syllable-timed and stress-timed rhythms. These features significantly impact intelligibility in cross-cultural communication. Conclusion. Phonological variations not only contribute to the rich diversity of global English but also play a crucial role in shaping the social and cultural identity of speakers. At the same time, these variations influence the effectiveness of communication across cultural and linguistic boundaries.